Tax Knowledge, Tax Sanctions, Field Raids, Moral Responsibility, and Economic Conditions on Motor Vehicle Taxpayers' Compliance at the Badung Samsat Office - DEWI, Ni Luh Putu Sandrya; MENDRA, Ni Putu Yuria; DANIYANTI, Ni Made Windi Egi (Journal of Entrepreneurial and Business Diversity, 2025)
Purpose:Ensuring people abide by tax laws is critical, as failure to do so often results in attempts to avoid paying taxes, ultimately diminishing government revenues. Taxpayers who willingly adhere to these regulations fulfill their tax duties, streamlining the government's tax collection procedures.Methodology:This research aimed to investigate how the comprehension of tax-related details, penalties, on-site inspections, moral responsibilities, and economic conditions affect compliance among motor vehicle taxpayers at the Badung Samsat Office. The study encompassed a population of 543,013 registered motor vehicle taxpayers at the Badung Regency Samsat office as of December 31, 2022. A sample of 100 taxpayers was used for the research. The analytical approach employed in this study was multiple linear regression analysis.Findings:The findings of the study suggest that on-site inspections, moral responsibilities, and economic circumstances significantly influence compliance with motor vehicle taxes at the Badung Samsat Office. However, the understanding of tax information and penalties did not impact compliance among these taxpayers.Implication:Based on the result, with field examination, moral responsibility and economic conditions can make taxpayers comply with their tax obligations.